Pelatihan Desain Grafis bagi Siswa SMK Global Persada Mandiri Bekasi - Hiswara, Abrar; Noe’man, Achmad (Journal Of Computer Science Contributions (JUCOSCO), 2022)
Graphic design is a communication process using visual elements, such as typography, photography, and illustrations that are intended to create a perception of a message being conveyed. This field involves the process of visual communication and communication design and is very much needed by today's society, including students at SMK Global Persada Mandiri Bekasi. The material provided in this graphic design training is an introduction to graphic design, the benefits of graphic design, types of graphic design, and the practice of making graphic designs, in the form of logos, banners, and flyers. This graphic design training in the form of logo creation training provides tremendous benefits for students. Students can design any logo so that their soft skills increase and can be used in everyday life.